2022
DOI: 10.3389/fonc.2022.884474
|View full text |Cite
|
Sign up to set email alerts
|

HAMP as a Prognostic Biomarker for Colorectal Cancer Based on Tumor Microenvironment Analysis

Abstract: Colorectal cancer (CRC) is the most common digestive tumor in the world and has a high mortality rate. The development and treatment of CRC are related to the immune microenvironment, but immune response-related prognostic biomarkers are lacking. In this study, we used The Cancer Genome Atlas (TCGA) to explore the tumor microenvironment (TME) and weighted gene coexpression network analysis (WGCNA) to identify significant prognostic genes. We also identified differentially expressed genes in the TCGA data and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…It is shown that HAMP is closely associated with immune regulation ( 55 ), and our enrichment analysis results suggested that HAMP-related genes are mostly engaged in immune activation pathways (cytokine-cytokine receptor interactions, chemokine signaling pathways) in CRC. However, in CRC, the relevance of HAMP to immune cell infiltration and stromal cells in the TME is still unclear.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…It is shown that HAMP is closely associated with immune regulation ( 55 ), and our enrichment analysis results suggested that HAMP-related genes are mostly engaged in immune activation pathways (cytokine-cytokine receptor interactions, chemokine signaling pathways) in CRC. However, in CRC, the relevance of HAMP to immune cell infiltration and stromal cells in the TME is still unclear.…”
Section: Discussionmentioning
confidence: 70%
“…Our results showed that upregulation of HAMP is associated with DNA mismatch repair genes, TMB, and MSI with different cancers, demonstrating the crucial role of HAMP in predicting the effects of immunotherapy. It is shown that HAMP is closely associated with immune regulation (55), and our enrichment analysis results suggested that HAMP-related genes are mostly engaged in immune activation pathways (cytokine-cytokine receptor interactions, chemokine signaling pathways) in CRC. However, in CRC, the relevance of HAMP to immune cell infiltration and stromal cells in the TME is still unclear.…”
Section: Discussionmentioning
confidence: 72%
“…It is well known that HAMP plays an essential negative role in iron homeostasis, and its production of hepcidin was proven to be expressed in many cancers and non-cancer tissues [14,15]. In addition, a previous study showed that HAMP induced aggressive hepatocellular carcinoma (HCC), colorectal cancer (CRC) and skin cutaneous melanoma (SKCM), so we can infer that HAMP may be a potential prognostic and diagnostic biomarker for KIRC [16][17][18].…”
Section: Introductionmentioning
confidence: 92%